2007
DOI: 10.1021/jf072704z
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Large-Scale Purification of Yessotoxin from Protoceratium reticulatum Culture and Isolation of a Novel Furanoyessotoxin

Abstract: Yessotoxins from a large-scale culture (226 L) of Protoceratium reticulatum strain CAWD129 were harvested by filtration followed by solid-phase extraction. The extract was purified by column chromatography over basic alumina and reverse-phase flash chromatography to afford pure yessotoxin (193 mg). Isolation of yessotoxin was greatly facilitated by selection of a strain which did not produce analogues that interfered with yessotoxin isolation. In addition to yessotoxin, numerous minor yessotoxins were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The major impurity (2.8%) was an isomer of AZA1, while AZA3 and dehydro-AZA3 were present at 0.4 and 0.7%, respectively. YTX was purified and stored in methanol solution to prevent decomposition as described by Loader et al (2007). The purity of this material was estimated to be >95% from NMR analysis (see supporting information from Loader et al (2007)) and its concentration was determined by LC-MS/MS analysis relative to a certified standard of YTX from NRC (NRC-CNRC, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major impurity (2.8%) was an isomer of AZA1, while AZA3 and dehydro-AZA3 were present at 0.4 and 0.7%, respectively. YTX was purified and stored in methanol solution to prevent decomposition as described by Loader et al (2007). The purity of this material was estimated to be >95% from NMR analysis (see supporting information from Loader et al (2007)) and its concentration was determined by LC-MS/MS analysis relative to a certified standard of YTX from NRC (NRC-CNRC, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…YTX was purified and stored in methanol solution to prevent decomposition as described by Loader et al (2007). The purity of this material was estimated to be >95% from NMR analysis (see supporting information from Loader et al (2007)) and its concentration was determined by LC-MS/MS analysis relative to a certified standard of YTX from NRC (NRC-CNRC, 2006). (Table 1) of the YTX stock solutions were dispensed into vials, which were capped and stored at −20 °C until required for preparation of doses.…”
Section: Methodsmentioning
confidence: 99%
“…Dinoflagellates have proved difficult to mass culture and this has limited the supply of their bioactives for investigational purposes . The dinoflagellate Protoceratium reticulatum has been used as a model to better understand some of the important aspects of mass culturing these fragile microalgae (Gallardo Rodríguez et al, 2009, 2010García Camacho et al, 2007;Guerrini et al, 2007;Loader et al, 2007;Paz et al, 2006Paz et al, , 2009Rodríguez et al, 2007Rodríguez et al, , 2009 . Media that have been conventionally used for culturing the common industrial microalgae, are not appropriate for growing dinoflagellates. For example, a recent study demonstrated that the levels of phosphate and nitrate found in the basal L1 medium were unsatisfactory for efficiently culturing P. reticulatum and producing its bioactives (Gallardo Rodríguez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Yessotoxins (YTXs) (Figure 7) are produced by the dinoflagellates Proceratium reticulatum and Lingulodinium polyedrum [39,76]. Until now up to 90 YTX analogues have been identified [77].…”
Section: Poisoning Syndromes and Corresponding Toxinsmentioning
confidence: 99%